Swallowing and Liking of Vegetable-Enriched Bread Compared With Commercial Breads as Evaluated by Older Adults - Amoah, Isaac; Cairncross, Carolyn; Rush, Elaine (Frontiers in Nutrition, 2021)
Characteristics of food that influence liking and ease-of-chewing and swallowing are not well understood. Reformulation of bread to improve nutrient density may improve liking, ease-of-chewing and swallowing which could improve dietary intake particularly with aging. The study aimed to compare objectively and subjectively four breads of increasing nutrient density: $1 white (WB) and wheatmeal (WMB) commercial breads and two in-house formulations of vegetable-enriched breads (VB75 or VB100) which incorporated drum-dried pumpkin and sweet corn flours for physical, sensory and ease-of-chewing and swallowing properties. Each bread underwent instrumental texture analysis. The commercial and vegetable-enriched breads were not different by hardness or springiness but the vegetable breads were up to 25% less cohesive, less gummy and less chewy than the commercial breads. Questionnaires and Likert scale (150mm) responses were completed by 50 physically active volunteers aged 50+ years. Overall liking of the VB75 and VB100 was rated as 40% higher than the white and wheatmeal breads. Vegetable-enriched breads were rated as almost 50% easier to chew (mean±SD; WB 70.53±39.46mm, WMB 77.68±33.13mm, VB75 104.78±30.69mm, VB100 107.58±24.90mm) and swallow (WB 70.29±37.98mm, WMB 77.53±34.88mm, VB75 104.63±28.25mm, VB100 104.90±25.54mm). Vegetable-enriched breads compared to white and wheatmeal breads were instrumentally and subjectively less gummy, cohesive and chewy than commercial breads and have the potential to both improve nutrition and ‘ease of swallowing’ in older people. New areas of research should explore other underutilised vegetables for bread enrichment and their ability to aid swallowing and improve nutrition status.